Compliance-Innovation: Supporting Regional Growth - Eleanor Doyle; Damien McGovern; Stephen McCarthy (European Regional Science Association (ERSA), 2013)
Strategic growth can be delivered through Innovative Compliance a process through which conformity with requirements - compliance - drives improvements in quality, productivity and competitiveness. In this process GRC is an engine for growth by facilitating commercialisation of knowledge and business sustainability. The integration of Governance, Risk & Compliance (GRC) with Innovation activities and business strategy is what we mean by strategic growth. Maintaining attention and focus on growth is a challenge for business in the face of increasing demands on Boards and Directors to address not only considerably more but increasingly complex types of risks. At the same time, capacity to adapt and reconfigure resources in response to market challenges, regulatory reform and complex stakeholder influences and expectations is necessary to achieve the strategic growth businesses need. Innovation can be driven by a company?s GRC orientation in the context of its corporate GRC memory as well as its business strategy supported appropriately with technology. We term this orientation Innovative Compliance. One vital element for Innovative Compliance is access to timely regulatory-compliance data structured in line with a business?s product, market and geography focus: decision makers need actionable information. Modern IT makes this increasingly possible which is particularly welcome since much of the regulation aimed at business is not provided in a format or through channels or in a timely fashion to meet businesses? information needs. A further necessity for Innovative Compliance is the ability of business to assimilate and transform regulatory and compliance data so that it can be exploited for commercial ends. This depends on an organisation?s Absorptive Capacity. In specifically GRC terms Absorptive Capacity gets at the ability to nail the various intersections of three fast moving business targets i.e. (i) new regulations (ii) product evolution (new & improved) and (iii) intra-organisational strategic imperatives. IT must simultaneously support all three aspects. Knowledge integration is the basis of modern competitive advantage and the strategic growth orientation of the business is the governing force for such integration. Modern Compliance Knowledge Management Systems can support this imperative. To operationalize Innovative Compliance executives must bring together teams of knowledge workers who are differentiated by their knowledge bases and support them to integrate the knowledge across the bases. The nature and extent of integration must resonate with the business reality of growth-oriented GRC functional experts, whatever their title, domain or expertise. In the absence of such integration ? GRC, Innovation, IT and Strategy ? productive growth opportunities are being missed.
Keywords: O; 330